2016
DOI: 10.1093/ije/dyw238
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neonatal vitamin A supplementation on morbidity and mortality at 12 months: a randomized trial

Abstract: Background: Neonatal vitamin A supplementation (NVAS) is an intervention hypothesized to reduce infant morbidity and mortality. The objective of this study was to assess the efficacy of neonatal vitamin A supplementation in reducing infant morbidity and mortality and assess potential sources of heterogeneity of the effect of NVAS. Methods: We completed an individually randomized, double-blind, placebo-controlled trial in Tanzania. Infants were randomized within 3 days of birth to a single dose of vitamin A (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Vitamin A supplementation was not independently associated with mortality in SAM patients at multivariate analysis. This is in agreement with the findings by Smith et al (15) in Tanzania (P = 0•54; CI 0•92-1•16).…”
Section: Discussionsupporting
confidence: 93%
“…Vitamin A supplementation was not independently associated with mortality in SAM patients at multivariate analysis. This is in agreement with the findings by Smith et al (15) in Tanzania (P = 0•54; CI 0•92-1•16).…”
Section: Discussionsupporting
confidence: 93%
“…However, the validity of postpartum MVAS programmes as a proxy for maternal vitamin A status is not clear, as it may depend on a mother’s pre-existing level of VAD and quality of programme implementation. In fact, a subgroup analysis among participants in the Tanzania trial found that the effect of NVAS was modified by both postpartum MVAS and the amount of vitamin A that women consumed through food 39…”
Section: Discussionmentioning
confidence: 99%
“…Maternal vitamin A status can also modify infant outcomes. 43 We were therefore careful in our study to include only those infants born to mothers randomised to the placebo arm.…”
Section: Discussionmentioning
confidence: 99%